Factors Affecting Bank Profitability in Pakistan - AKHTAR WADOOD; MUHAMMAD TAHIR KHAN; FAIZA SALEEM; SAQIB SHAHZAD (Journal of Business & Tourism, 2021)
The role that banks as key intermediaries play in the modern economy activities is unquestionable, it is admitted that banks remain one of the key financial intermediaries that provide a variety of services in the economy of every state. However, not all financial intermediaries have a significant impact on modern economies, only a stable and profitable banking sector can adequately play the role of financial intermediary in economy. The purpose of this research is to examine the relationship between bankspecific and macro-economic characteristics over bank profitability by using data of top fifteen Pakistani commercial banks over the period 2011-2016. This research we used the Ordinary Least Square (OLS) method to investigate the impact of assets, non-performing loans, equity, economic growth, interest rate and market capitalization on major profitability indicators i.e., return on asset (ROA), return on equity (ROE), return on capital employed and net interest margin separately. The empirical results have found strong evidence that both internal and external factors have a strong influence on the profitability. In conclusion, the empirical result shows that the bank specific factors are directly controlled by the Management thereby it has a positive correlation to the bank profitability while the industry specific (market concentration) also positively affects the bank profitability.